2009
DOI: 10.1175/2009mwr2827.1
|View full text |Cite
|
Sign up to set email alerts
|

Convective-Scale Downdrafts in the Principal Rainband of Hurricane Katrina (2005)

Abstract: Airborne Doppler radar data collected during the Hurricane Rainband and Intensity Change Experiment (RAINEX) document downdrafts in the principal rainband of Hurricane Katrina (2005). Inner-edge downdrafts (IEDs) originating at 6-8-km altitude created a sharp reflectivity gradient along the inner boundary of the rainband. Low-level downdrafts (LLDs) evidently driven by precipitation drag originated at 2-4 km within the heavy rain cells of each convective element. The IED and LLD were spatially separated by but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
76
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 43 publications
8
76
0
Order By: Relevance
“…A pronounced radially inward flow penetrated E2 and subsided into the base of the convective cell. The flow pattern associated with the downdraft having a speed of 2 m s −1 was comparable with the low level downdraft, which emanated from 2-4 km levels, described by Didlake and Houze (2009). Figure 15 shows the vertical characteristics of E4 along the H-H' radial line with respect to the typhoon center (depicted in Fig.…”
Section: Vertical Characteristics Of Convectionmentioning
confidence: 69%
See 1 more Smart Citation
“…A pronounced radially inward flow penetrated E2 and subsided into the base of the convective cell. The flow pattern associated with the downdraft having a speed of 2 m s −1 was comparable with the low level downdraft, which emanated from 2-4 km levels, described by Didlake and Houze (2009). Figure 15 shows the vertical characteristics of E4 along the H-H' radial line with respect to the typhoon center (depicted in Fig.…”
Section: Vertical Characteristics Of Convectionmentioning
confidence: 69%
“…The reflectivity gradient was sharp at the radially inner side of E1, where a significant downdraft (>2 m s −1 ) at 10-15 km in the horizontal coordinate originated below 6 km in altitude. The pattern suggested that the downdraft resembled an inner edge downdraft proposed by Didlake and Houze (2009), who explained that the inner-edge downdraft was driven by the buoyancy-induced pressure gradient acceleration originating at 6-8 km altitude, creating a significant reflectivity gradient along the inner boundary of the rainband. However, the convective core E1 tilted radially inward and updrafts tilted radially outward.…”
Section: Vertical Characteristics Of Convectionmentioning
confidence: 70%
“…Yet other possibilities may exist. One of them is a line or cluster of quasistationary or back-building convection generated by the collision of the outflow from storm-generated cold pools and the prevailing flow at the cold-pool boundary (Doswell et al, 1996;Schumacher and Johnson, 2005;Didlake and Houze, 2009;Houze, 2010). Apparently additional investigations are warranted.…”
Section: Model Simulation and Discussionmentioning
confidence: 99%
“…The concentration of downdrafts seen here higher aloft suggests that they are related to alternative mechanisms, such as the pressure gradient response to buoyancy or the shear-relative flow (Houze 1993, chapter 7;Yuter and Houze 1995;Bender 1997;Frank and Ritchie 1999;Didlake and Houze 2009). Another potential downdraft source is the detrainment of air within hot towers.…”
Section: July 2014 D E H a R T E T A Lmentioning
confidence: 93%
“…Strong downdrafts DL and UR concentrate along the edges of the eyewall. The midlevel maximum of downdraft occurrence DL strongly suggests that they may result from potential mechanisms such as dynamical forcing in response to the high-altitude convective updrafts or detraining air from the intense convection (Houze 1993, chapter 7;Yuter and Houze 1995;Bender 1997;Frank and Ritchie 1999;Heymsfield et al 2001;Didlake and Houze 2009). The intense downdrafts UL maximize in frequency on the inner edge of the eyewall, which could at least partially be a result of the radar signal becoming too weak because of radar attenuation.…”
Section: July 2014 D E H a R T E T A Lmentioning
confidence: 99%